Prepubertal castration‐associated developmental changes in sigma‐1 receptor gene expression levels regulate hippocampus area CA1 activity during adolescence. Issue 7 (27th February 2016) - Moradpour, Farshad; Fathollahi, Yaghoub; Naghdi, Nasser; Hosseinmardi, Nargess; Javan, Mohammad
ABSTRACT: The functional relevance of sigma‐1 (σ1 ) receptor expression in the rat hippocampal CA1 during adolescence (i.e., 35–60 days old) was explored. A selective antagonist for the σ1 receptor subtype, BD‐1047, was applied to study hippocampal long‐term potentiation (LTP) and spatial learning performance. Changes in the expression of the σ1 receptor subtype and its function were compared between castrated and sham‐castrated rats. Castration reduced the magnitude of both field excitatory postsynaptic potential (fEPSP)‐LTP and population spike (PS)‐LTP at 35 days (d). BD‐1047 decreased PS‐LTP in sham‐castrated rats, whereas BD‐1047 reversed the effect of castration on fEPSP‐LTP at 35 d. In addition, BD1047 impaired spatial learning and augmented σ1 receptor mRNA levels in castrated rats at 35 d. Surprisingly, neither castration nor BD1047 had an effect on fEPSP‐LTP and PS‐LTP, spatial learning ability or gene expression levels at 45 d. Castration had no effect on fEPSP‐LTP but reduced PS‐LTP at 60 d. BD1047 increased the magnitude of fEPSP‐LTP, but had no effect on PS‐LTP in castrated rats at 60 d. However, BD1047 reduced spatial learning ability, and σ1 receptor mRNA levels were decreased in castrated rats at 60 d. This study shows that σ1 receptors play a role in the regulation of both CA1 synaptic efficacy and spatial learning performance. The regulatory role of σ1 receptors in activity‐dependent CA1‐LTP is locality‐ and age‐dependent, whereas its role in spatial learning ability is only age‐dependent. Prepubertal castration‐associated changes in the expression and function of the σ1 receptor during adolescence may play a developmental role in the regulation of hippocampal area CA1 activity and plasticity. © 2016 Wiley Periodicals, Inc.